Stereotypes about New Zealand : culture, contact, and national identity : a thesis presented in partial fulfilment of the requirements for the degree of Master of Management in Communication Management at Massey University - Sander, Mischa (Massey University, 2004)
From a sociocultural perspective, this study aims to describe stereotypes about New Zealand and New Zealanders and to compare them to New Zealanders' self-perceptions. Objectives are to determine whether differences across cultures exist that relate to stereotypes and how stereotype use and content relate to the amount of contact with New Zealanders. An extensive review of literature introduces general and intercultural concepts of stereotypes and links them to the national identity of New Zealanders. Focus group interviews and a qualitative pilot study are conducted in order to prepare and test an online survey targeted to young, educated people from selected Western cultures. More than 1,100 people participated, including New Zealanders, tourists, international students studying in New Zealand, and people who had not been to New Zealand at all. Results indicate that increased contact with New Zealanders may increase stereotype use. People who have not been to New Zealand mainly hold traditional stereotypes, whereas New Zealanders differentiate more between reality and stereotypical myths. As such, contact is closely related to stereotype use and content. By contrast, cultural membership shows no relation to stereotyping. Further, a theoretical framework, adapted from the Johari window, is developed that links stereotypes, national identity, and national image. As the study is limited because of non-random sampling techniques, its findings cannot be generalised to a larger population. Indications for future research opportunities include the use of larger random samples, particularly of alternative cultures, the application of qualitative measures, and the suggestion to replicate the theoretical framework.
Keywords: National characteristics; New Zealand; Intercultural communication; Stereotype (Psychology); Tourists; Attitudes